Why don't segregated Roma do more for their health? An explanatory framework from an ethnographic study in Slovakia - Belak, Andrej; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of public health, 2018)
OBJECTIVES: The health status of segregated Roma is poor. To understand why segregated Roma engage in health-endangering practices, we explored their nonadherence to clinical and public health recommendations. METHODS: We examined one segregated Roma settlement of 260 inhabitants in Slovakia. To obtain qualitative data on local-level mechanisms supporting Roma nonadherence, we combined ethnography and systematic interviewing over 10 years. We then performed a qualitative content analysis based on sociological and public health theories. RESULTS: Our explanatory framework summarizes how the nonadherence of local Roma was supported by an interlocked system of seven mechanisms, controlled by and operating through both local Roma and non-Roma. These regard the Roma situation of poverty, segregation and substandard infrastructure; the Roma socialization into their situation; the Roma-perceived value of Roma alternative practices; the exclusionary non-Roma and self-exclusionary Roma ideologies; the discrimination, racism and dysfunctional support towards Roma by non-Roma; and drawbacks in adherence. CONCLUSIONS: Non-Roma ideologies, internalized by Roma into a racialized ethnic identity through socialization, and drawbacks in adherence might present powerful, yet neglected, mechanisms supporting segregated Roma nonadherence.
Keywords: Cross-Sectional Studies; Male; Slovakia; rozhovory jako téma; Ethnographic study; Interviews as Topic; Slovenská republika; Roma health; chudoba; Poverty; Roma; Racism; Anthropology, Cultural; mužské pohlaví; Romové; kulturní antropologie; rasismus; Health inequality; Health Status; lidé; ženské pohlaví; Humans; průřezové studie; zdravotní stav; společenské stigma; Female; Adherence; Social Stigma